1999
DOI: 10.1002/(sici)1097-4571(1999)50:3<207::aid-asi3>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

A theory of life in the round

Abstract: This study addresses ways in which inmates at the only maximum‐security prison for women in Neuse City (in the northeastern United States) redefine their social world in order to survive incarceration. An aim of the project is to engage in theory building in order to examine the experiences of a world that is “lived in the round.” A life in the round is a public form of life. It is a lifestyle with an enormous degree of imprecision. Yet, it is this inexactitude that provides an acceptable level of certainty. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
268
0
46

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(322 citation statements)
references
References 16 publications
8
268
0
46
Order By: Relevance
“…In terms of the information behavior literature, sociospatial aspects of context have been dealt with by a small number of researchers. Our research emphasizes the focus provided by Fisher et al (2004), Pettigrew (1999), Chatman (1992Chatman ( , 1999, and others that deals with the sociospatial context of information behavior on the absolute significance of social relationships in information-seeking activities within a spatial context. Our work extends and develops this research, implying a form of spatial and temporal compression that occurs within ad hoc mobile information grounds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of the information behavior literature, sociospatial aspects of context have been dealt with by a small number of researchers. Our research emphasizes the focus provided by Fisher et al (2004), Pettigrew (1999), Chatman (1992Chatman ( , 1999, and others that deals with the sociospatial context of information behavior on the absolute significance of social relationships in information-seeking activities within a spatial context. Our work extends and develops this research, implying a form of spatial and temporal compression that occurs within ad hoc mobile information grounds.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has emphasized changes in spatial regularities enabled by technologies (c.f. Castells, 1998Castells, , 2007 leading, some have argued, to the death of place or a reconstitution of our existing understanding of the relationship between space and place (Graham, 1998) Within the field of information behavior, however, the approach has been primarily subjectivist and qualitative and developed by two key researchers-Chatman (Chatman, 1987(Chatman, , 1991(Chatman, , 1992(Chatman, , 1996(Chatman, , 1999 and Pettigrew/née Fisher (Fisher et al, 2004;Pettigrew, 1999;Pettigrew et al, 2001) -in the context every-day information behavior. Using a social constructionist approach, Fisher and colleagues have argued that the study of information cannot be considered outside its social context (Fisher et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the reasons for low health information seeking on the Internet may be related to the life experiences of this community such as the 'small-world' phenomenon identified by Chatman. 19,20 Research conducted prior to widespread use of the Internet examined the information-use environment of underserved populations such as the patients served by the centre and found that information seeking from sources outside the boundaries of the community is less prevalent than information seeking from perceived authoritative sources within the community. This phenomenon may affect patterns of information seeking, particularly in areas such as health-related topics.…”
Section: Regardless Of Recent Changes In Technologymentioning
confidence: 99%